Seed Layers for the Growth of Oriented Vertical Arrays of ZnO Nanorods. (23rd January 2018) - Cernohorsky, Ondrej; Grym, Jan; Yatskiv, Roman; Schenk, Antonin; Chlupova, Sarka; Maixner, J; Vanis, Jan; Basinova, Nikola; Roesel, David
Abstract : We report on the preparation of one-dimensional rod-like ZnO nanostructures by chemical bath deposition on seed layers prepared by two processes: electrophoretic deposition and sol-gel process. Morphological and structural properties of both, the seed layers and ZnO nanorods, were studied by scanning electron microscopy (SEM) and x-ray diffraction (XRD). Hexagonally ordered arrays of vertically oriented ZnO nanorods were prepared by electron beam lithography.